2019
DOI: 10.12740/app/109754
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and psychological well-being in cardiac patients: Is the association mediated by self-efficacy?

Abstract: Aim of the study:A large deal of research on cardiac patients concentrates on analyses of mutual relationships between sense of coherence and psychological well-being, sense of coherence and self-efficacy, or psychological well-being and self-efficacy. It has been proven that self-efficacy plays a crucial role as a mediator of the relationships between various psychological constructs. Material and method:A total number of 176 patients (82 women and 94 men), age 45-82 years (M = 58.56, SD = 8.25) participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Empirical support for the usefulness of enhancing both SOC and self-efficacy in individuals as means toward health promotion was provided in a national Danish survey ( Trap et al , 2016 ). Further analysis of the relationship between SOC and self-efficacy was reported recently by Krok and Kleszczewska-Albańska, who found that SOC had a strong direct effect on psychological well-being but was also partially mediated by self-efficacy ( Krok and Kleszczewska-Albańska, 2019 ).…”
Section: Introductionmentioning
confidence: 73%
“…Empirical support for the usefulness of enhancing both SOC and self-efficacy in individuals as means toward health promotion was provided in a national Danish survey ( Trap et al , 2016 ). Further analysis of the relationship between SOC and self-efficacy was reported recently by Krok and Kleszczewska-Albańska, who found that SOC had a strong direct effect on psychological well-being but was also partially mediated by self-efficacy ( Krok and Kleszczewska-Albańska, 2019 ).…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, paying attention to the positive psychological variables in dealing with CoViD anxiety can be important. Among these variables, we can mention the sense of cohesion, which is the ability of a person to identify the stressors of life, as well as the efficient use of coping resources and maintaining health [26]. This feeling is a personal orientation towards life.…”
Section: Appreciationmentioning
confidence: 99%
“…Related findings on SoC and SWB were reported in Croatia [26,58], Norway [24,27,51], Turkey [59], and Poland [60,61]. Extant researchers have also produced inconsistent findings.…”
Section: Introductionmentioning
confidence: 97%